Algorithm of Generalization of the rule counting the number of the free variables (parameters) in Singly–Even Pandiagonal Magic Squares (Journal of the College of Basic Education, 2022)
In this paper, we put the algorithm of generalization the rule of counting the number of the free variables (parameters) in the Singly–Even Pandiagonal magic square; our method is not based on the direct computation of the solution of the linear system. Instead, We deduce this rule by applying the theorems and methods of linear algebra.